Zoë bakes cakes : everything you need to know to make your favorite layers, bundts, loaves, and more - François, Zoë (Ten Speed Press, 2021)
An expert baker and the best-selling author of Artisan Bread in Five Minutes a Day offers 100 easy-to-follow cake recipes including Apple Cake with Honey-Bourbon Glaze, Lemon Curd Pound Cake, Coconut Candy Bar Cake and Chocolate Devil’s Food Cake.